If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(5x + 3) + -11 = -9x + 11 + -6x + -19 Reorder the terms: 5(3 + 5x) + -11 = -9x + 11 + -6x + -19 (3 * 5 + 5x * 5) + -11 = -9x + 11 + -6x + -19 (15 + 25x) + -11 = -9x + 11 + -6x + -19 Reorder the terms: 15 + -11 + 25x = -9x + 11 + -6x + -19 Combine like terms: 15 + -11 = 4 4 + 25x = -9x + 11 + -6x + -19 Reorder the terms: 4 + 25x = 11 + -19 + -9x + -6x Combine like terms: 11 + -19 = -8 4 + 25x = -8 + -9x + -6x Combine like terms: -9x + -6x = -15x 4 + 25x = -8 + -15x Solving 4 + 25x = -8 + -15x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '15x' to each side of the equation. 4 + 25x + 15x = -8 + -15x + 15x Combine like terms: 25x + 15x = 40x 4 + 40x = -8 + -15x + 15x Combine like terms: -15x + 15x = 0 4 + 40x = -8 + 0 4 + 40x = -8 Add '-4' to each side of the equation. 4 + -4 + 40x = -8 + -4 Combine like terms: 4 + -4 = 0 0 + 40x = -8 + -4 40x = -8 + -4 Combine like terms: -8 + -4 = -12 40x = -12 Divide each side by '40'. x = -0.3 Simplifying x = -0.3
| 5x+4+57+64=180 | | 1890+1240y=9100 | | 3.5=a(x-0)(x-1.5) | | 5(5x+3)-11=-x+11-6x-19 | | 3.5=a(x-e)(x-7.1) | | 35c-25c= | | x/2+x/4=1/8 | | C=xy+b | | (0.125x^4)+(2.5x^2)+3=0 | | 3.5=a(7.1-e)(7.1-7.1) | | x+y=4x-40 | | 0.125x^4+2.5x^2+3=0 | | U^10=100 | | 4.7h=30.55 | | 4y-5x=17 | | y=a(x-h)(x-h)+3.5 | | -3x+2=18 | | x^4+2x^3-x^2=0 | | -29+x=41 | | 36b-4b= | | 3.5=a(7.1-h)(7.1-h)+3.5 | | 22.2+2x=98 | | 210x+1240y=9100 | | 74+20=450+20x | | 3.2r+14.7=-6.47 | | 3.5=a(7.1-h)2+3.5 | | 74+20*x=450+20x | | 37=-3+5(5x+6) | | m+5(5-1)=7 | | 7x+4+7x+2+2=120 | | 12x+3.35=8.75 | | f(x)=2x^2-16x+67 |